Efektivitas Layanan Bimbingan Kelompok Menggunakan Teknik Cognitive Behavior Therapy (CBT) untuk Meningkatkan Kemandirian Belajar Remaja - Fadil Maiseptian; Erna Dewita; Rosdialena Rosdialena (IAIN Manado, 2022)
The Effectiveness of Group Guidance Services Using Cognitive Behavior Therapy (CBT) Techniques to Improve Adolescent Learning Independence. This study aims to determine the differences in the learning independence of adolescents in the experimental and control groups after being given group guidance services using cognitive behavior therapy techniques. This quantitative study used a quasi-experimental design with a non-equivalent control group design. The research subjects were teenagers from the Aisyiyah Orphanage Koto Tangah Ampang, Padang City. Determination of research subjects using the purposive sampling technique. The instrument used in this study was a learning independence scale with an average validity of 0.001 and reliability of 0.938. Data analysis used the Wilcoxon signed ranks test and the Kolmogorov Smirnov 2 independent sample. The results showed that there were differences in scores on the pretest and posttest of the experimental group after being given group guidance services using CBT techniques to increase adolescent learning independence. Then, there was no difference in scores in the pretest and posttest of the control group after being given group guidance services without the CBT technique. Furthermore, there are differences in the posttest scores of the experimental and control groups after being given group guidance services using CBT techniques.